Evaluación del proceso para la obtención de extracto de semilla de guayaba (Psidium Guajava L.) Para su uso en la industria alimentaria (2023)
The objective of this theoretical-experimental research is to evaluate the process of obtaining guava seed extract by the Soxhlet method for use in the food industry, with the intention of taking advantage of the bioactives, antioxidants and fatty acids contained in said organic waste. coming from the sandwich industries. A bibliographic review of the generalities of guava was carried out, as well as the physicochemical characteristics and properties of its seeds, in addition to the sources of obtaining said residues in Colombia. After that, information was collected about experimental research focused on ESG. Secondly, the raw material was characterized and a detailed monitoring of the factors that influence the final quality of the extract was carried out, to establish the appropriate operating conditions of the process. Using an ANOVA, the influence of drying time and the variety of guava was studied against the yields of the extract, resulting in an average yield of 3.418%.